On dissociation in weakly doped ice - Chikina, I.; Shikin, V. (Физика низких температур, 2015)
Currently, there is some ambiguity in the problem of decay of a single donor into charged fragments. Thus, in the well-known Ostwald approximation used for semiconductors (ice being one of them) the donor dissociation degree of tends to its maximum value (i.e., unity) as the doping impurity concentration approaches zero. At the same time, the statistical theory of atom reveals within the Thomas–Fermi (or Debye–Hückel) approximation the existence of a thermodynamically equilibrium state of a single multi-electron atom (donor) where charged nucleus keeps the number of counterions just necessary for its neutralization. These scenarios do not show the atom dissociation at all. Discussed in the present paper is the alternative between the full dissociation of a single donor (i.e., dissociation degree equals unity) in a semiconducting media (ice, water, semiconductor) and zero dissociation degree.